1987
DOI: 10.2134/agronj1987.00021962007900060014x
|View full text |Cite
|
Sign up to set email alerts
|

Water Deficit Effects on Transpiration and Leaf Growth1

Abstract: Reductions of leaf development and transpiration are closely related to soil water deficits. Few studies have analyzed the effects of water deficits on both processes during different growth stages. A study was conducted to analyze and quantify the effects of water deficits during different growth stages on leaf development (number, extension, and senescence) and transpiration rates of sorghum [Sorghum bicolor (L.) Moench] and cotton (Gossypium hirsutum L.). The study was conducted at the Blackland Research Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
0
11

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 7 publications
8
46
0
11
Order By: Relevance
“…Further work is required to determine the dependence of a on pasture and soil types. If a can be successfully related to pasture species, this may provide a means to study the relative response of alternative pasture species to drought conditions (Parry et al 1992), as plant stress is closely related to ^£7 (McAneney et al 1982;McAneney & Judd 1983;Parfitt et al 1985aParfitt et al , 1985bRosenthal et al 1987;Barker et al 1989;Sadras & Milroy 1996). This would then allow a practical model of plant growth response to water stress to be formulated.…”
Section: Resultsmentioning
confidence: 99%
“…Further work is required to determine the dependence of a on pasture and soil types. If a can be successfully related to pasture species, this may provide a means to study the relative response of alternative pasture species to drought conditions (Parry et al 1992), as plant stress is closely related to ^£7 (McAneney et al 1982;McAneney & Judd 1983;Parfitt et al 1985aParfitt et al , 1985bRosenthal et al 1987;Barker et al 1989;Sadras & Milroy 1996). This would then allow a practical model of plant growth response to water stress to be formulated.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that the relationship between SPI and NDVI can be explained with a linear relationship as long as the seasonality is taken into account, for example, by conducting correlation analyses individually for each month of the year. Because the relationship between precipitation and vegetation development differs between plant species (Rosenthal et al, 1987), the analyses were conducted separately for different land uses. First, the average SPEI, SPI and NDVI values of all pixels in each land use were determined for each month.…”
Section: Time Series Of Spei Spi and Ndvimentioning
confidence: 99%
“…Virtually all major processes contributing to crop yield including leaf gas exchange (Ritchie, Burnett & Henderson 1972;Ritchie 1973;Sinclair & Ludlow 1986;Kuppers, Kuppers & Schulze 1988), leaf growth (Sinclair 1986;Rosenthal et al . 1987;Lecoeur & Sinclair 1996;Muchow & Sinclair 1991) are inhibited late in stage I or in stage II of soil drying.…”
Section: Yield and Crop Water Usementioning
confidence: 99%